'De jour en jour / From day to day': Documenting Times of Self-Mourning in Hervé Guibert's La Pudeur ou l'impudeur (1990). Issue 2 (October 2016) - Elsner, Anna Magdalena
Abstract : Mourning is predominantly understood as an emotional process caused by the loss of a beloved other. This is challenged in this article on Hervé Guibert's 1990 La Pudeur ou l'impudeur, a documentary in which the author and photographer represents his physical and emotional suffering through the last stages of HIV-AIDS. The article explores this suffering via the idea of 'self-mourning', which denotes Guibert's reflection on his own mortality in the light of terminal illness. In particular, the article focuses on what happens to the notion of time in mourning against the backdrop of Gilles Deleuze and Jean-Luc Nancy.